PERAN SEKRETARIS DESA (GAMPONG) DALAM MENINGKATKAN PELAYANAN PUBLIK ADMINISTRASI PEMERINTAHAN DI GAMPONG PAYAROH, KECAMATAN DARUL IMARAH ACEH BESAR - Nurdin Yunus (Jurnal Transformasi Administrasi, 2021)
This study aims to explain the role of the Village Secretary in Gampong Payaroh Government Administration Services. This study used a descriptive qualitative approach, and data collection techniques were carried out by observation, interview and documentation techniques. The number of respondents as many as 10 people. This study uses the theory of gampong government administration in terms of service to the community, gampong government administration, and other matters related to gampong payaroh. The results showed that the administrative services provided by the Payaroh Aceh Besar gampong government in this case that handled the gampong administrative process, namely the Gampong secretary, still had several shortcomings. This can be seen from the performance of the Gampong secretary in managing correspondence in the administration of archives, reporting, financial affairs, government affairs, development, and society. There are several things that need to be paid attention to by the apparatus in this village in handling the administration of gampong government, namely improving performance and providing good service to the community by following existing government mechanisms and procedures.